ANALISIS PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SEPATU OLAHRAGA NIKE (Studi Pada Toko Sport Icon di Semarang ) - Muhammad Hafiz Yanuar, 10.05.51.0060 (Students Journal of Economic and Management, 2015)
Sports shoesare an important partin supportingsportsactivities. Of the manybrands ofsports shoes, NIKEis a brandsports shoesthat have beenrecognizedby the publicorreliabilitycan beexpected to meetthe needs ofthe communitythatis growing in linewith thecompetitionof sports shoeswitha variety ofother brands. This study about the effects of product quality, price perception and brand image on purchase decisions was done to analyze the consumers purchasing decisions at Sport Icon Shoesstore in Semarang. Data used in this study is primary data and secondary data. While the techniques used for data collection using questionaire by asking a number of written questions used to obtain informations from the respondents. The population in this study were consumers who made purchases decising making NIKE sports shoes at the Sport Icon Shoesstore in Semarang. Were who make purchases NIKE sports shoes at the Sport Icon store in Semarang. The sampling techniqueis donewiththe technique of